Functional foods as a strategic area for food producers - Berglund, Sofia (2005)
This study comprises an analysis of how French dairy producers use functional food products in order to strengthen their position toward the retail industry. Its considerable proportions, its excellence and its international orientation motivate the choice of the French dairy industry. Functional food is a group of food products that, in addition to their nutritional values, include a value added, consisting of a documented health effect. They are designed to be consumed as every day products and they are either a food product of a beverage.